An Electrochemical Investigation into the Redox Properties of Push‐Pull Dibenzodioxins and Comparative Analysis with Analogous Heteroacenes. Issue 47 (14th December 2022) - Raghava, Tanya; Bhavana, Purushothaman; Banerjee, Subhadeep
Abstract: A series of dibenzodioxins containing electron push‐pull groups were synthesized using simple methods and their spectroscopic and redox behavior was studied. Electrochemical experiments were performed to measure the redox potentials of the substituted dibenzodioxins. The role of individual molecular subunits in tweaking the redox potential values was delineated by comparing them with the electrochemical properties of analogous heteroacenes. In many cases, our redox potentials were found to be comparably low with that of many well‐known heteroacenes. Abstract : The redox behaviour of push‐pull dibenzodioxins with different electron‐donating and withdrawing groups was investigated using cyclic voltammetry. The role of individual substituent groups and heterocycles towards modulation of the oxidation and reduction potentials was delineated by comparison with literature examples. A structure‐property relationship was outlined which highlights the importance of dibenzodioxins as electroactive heteracenes.